Biography and Memory: Karel Gott in Czech Culture of Remembrance - Sixta, Václav (Dějiny – teorie – kritika, 2025)
Karel Gott (1939–2019) was one of the most popular singers and popstars in Czechoslovakia during 20th and 21st century. His autobiography and biographies on his life are very popular and thus they are suitable sources for research on the theories of biography and memory studies. This text compares his autobiography, Karel Gott: Má cesta za štěstím (2021) and the biography Gott: Československý příběh (2021), written by Pavel Klusák, and focuses primarily on their reception (reviews in mass media and on web platforms for readers). We consider how do differences in the genres of autobiography and biography influence the reception of certain books? How do these biographies get involved into current debates in memory studies? Through answering these questions, this text aims to examine the role of biographical writing in contemporary cultures of remembrance.